Sistem Pengiriman Informasi Pada Sasaran Tembak Dart (Dissapear Automatically Retaliatory Target) Menggunakan Gelombang Radio - Darjat, Darjat; Cristie, Meisach (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
Radio waves are natural resources that are limited in their use, therefore, utilization should be in accordance with the regulations set by government regulations.In the Military in the efforts to maintain the integrity of the state union indonesian republic should be ready in any situation and condition. Because the reason that every soldier must have the ability to battle, one of the firearm. Therefore required that both facilities to support the business. Currently DART (dissapear automatticaly reliatory target) or more familiar with the target shoot, shoot at the target is able to hide this himself and bring himself and the suit can give a reply if shot at the time of the specified target does not shoot.. At the end of this task will be made Dart that is able to give information to the user with more efficient with the ability to accommodate Dart still existing. At the end of the task that this information can only be obtained by viewing the objects directly target shoot is expected to be addressed, so that the user does not see objects directly target shoot, but only see a display information system only.Keywords: Display information, DART